PENGARUH MODEL MISSOURI MATHEMATICS PROJECT (MMP) TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATISSISWA - Ahmad Arsali; Syahrul Anwar; Muahor Zakaria (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aimed to determine the effect of Missouri Mathematics Project (MMP) learning model students’ mathematical problem solving skills and compare it with conventional learning method. This study was conducted at MTs Al-Rahmah, Serang City. The type of study used was True Eksperimental Design using Pretest-Posttest Control Group. The Samples size was 60 students from the total population of class VIII MTs Al-Rahmah which was taken randomly using sample random sampling technique. The results of this study showed that, (1) there was a significant effect of Missouri Mathematics Project (MMP) learning model on students’ mathematical problem solving skills with a tcount value of 21,498 > ttable = 2,048 which means Ho was rejected and (2) there was a significant difference in improving of mathematical problem solving skills between students used Missouri Mathematics Project (MMP) learning model and students used conventional learning model with a tcount value of 6,2454 > ttable = 2,048 which means H0 is rejected